Ratio Decidendiin Pretrial Decision Number 5/Pid.Pra/PN Mataram: Cancellation of Suspect Determination Due to Invalid Police Report - I Wayan Sukardiawan; Musmuliadin; Hajairin Hajairin (Bulletin of Community Engagement, 2026)
Ratio Decidendiin Pretrial Decision Number 5/Pid.Pra/PN Mataram: Cancellation of Suspect Determination Due to Invalid Police Report